Echoes of surrealism : challenging socialist realism in East German literature, 1945-1990 - Berendse, Gerrit-Jan, 1959- (Berghahn, 2021)
"For many artists and intellectuals in East Germany, daily life had an undeniably surreal aspect, from the numbing repetition of Communist Party jargon to the fear and paranoia engendered by the Stasi. Echoes of Surrealism surveys the ways in which a sense of the surreal infused literature and art across the lifespan of the GDR, focusing on individual authors, visual artists, directors, musicians, and other figures who have employed surrealist techniques in their work. It provides a new framework for understanding East German culture, exploring aesthetic practices that offered an alternative to rigid government policies and questioned and confronted the status quo"--